Dynamics and fluxes of organic carbon and nitrogen in two Guiana Shield river basins impacted by deforestation and mining activities. Issue 1 (7th December 2017) - Gallay, Marjorie; Mora, Abrahan; Martinez, Jean‐Michel; Gardel, Antoine; Laraque, Alain; Sarrazin, Max; Beaucher, Eric; Doudou, Jean‐Claude; Lagane, Christelle
Abstract: Deforestation and mining activities have proven to be very damaging to rivers because these activities disturb the environmental characteristics of rivers. Thus, the concentrations of dissolved organic carbon (DOC), particulate organic carbon (POC), particulate nitrogen (PN), and Chlorophyll‐a (Chl‐a) were measured monthly during 2 hydrological years in the Maroni and Oyapock Rivers to assess the dynamics and fluxes of organic carbon and nitrogen in these 2 Guiana Shield basins, which have been strongly (Maroni) and weakly (Oyapock) impacted by deforestation and mining activities. The 2‐year time series show that DOC, POC, PN, and Chl‐a concentrations vary seasonally with discharge in both rivers, indicating a hydrologically dominated control. Temporal patterns of DOC, POC, and PN indicate that these variables show maximum concentrations in rising waters due to the yield of organic matter and nitrogen accumulated in soils, which are incorporated into the rivers during rainfall. However, the Chl‐a concentrations were at a maximum during low‐water stages. The C/N and C/Chl‐a ratios also showed a seasonal trend, with lower values during the low water periods due to an increase in algal biomass. During high water, the POC in both rivers is the result of terrestrial organic matter, whereas during low‐water autochthonous organic matter can reach up to 34% of the POC. The mean annual fluxes of TOC and PN were higher (4.56 × 10 5  tonC year −1 and 1.77 × 10 4  tonN year −1, respectively) in the Maroni River than those (1.84 × 10 5  tonC year −1 and 0.54 × 10 4  tonN year −1, respectively) in the Oyapock River. However, the specific fluxes of DOC, POC, and PN from both basins were nearly the same. Although gold mining activities are performed in both basins, there is no conclusive evidence regarding the impact of these activities on the dynamics of organic matter and particulate nitrogen in the Maroni and Oyapock Rivers.